2008
DOI: 10.5194/bg-5-925-2008
|View full text |Cite
|
Sign up to set email alerts
|

Small scale controls of greenhouse gas release under elevated N deposition rates in a restoring peat bog in NW Germany

Abstract: Abstract. In Central Europe, most bogs have a history of drainage and many of them are currently being restored. Success of restoration as well as greenhouse gas exchange of these bogs is influenced by environmental stress factors as drought and atmospheric nitrogen deposition. We determined the methane and nitrous oxide exchange of sites in the strongly decomposed center and less decomposed edge of the Pietzmoor bog in NW Germany in 2004. Also, we examined the methane and nitrous oxide exchange of mesocosms f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
(60 reference statements)
1
16
1
Order By: Relevance
“…The relationship between the uptake of CO 2 by plants (GPP) and photosynthetically active radiation (PAR) can be modelled using the Michaelis-Menten-kinetics (Michaelis and Menten, 1913) and is known to vary greatly between plant species and individual plant development stages (Hall and Rao, 1999). Therefore, we estimated the parameters α (initial slope of the regression curve in mg CO 2 -C m −2 h −1 )/(µmol m −2 s −1 ) and GP max (limit of production rate when approaching infinite PAR in mg CO 2 -C m −2 h −1 ) for each measurement location per measurement date using Eq.…”
Section: Gpp Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between the uptake of CO 2 by plants (GPP) and photosynthetically active radiation (PAR) can be modelled using the Michaelis-Menten-kinetics (Michaelis and Menten, 1913) and is known to vary greatly between plant species and individual plant development stages (Hall and Rao, 1999). Therefore, we estimated the parameters α (initial slope of the regression curve in mg CO 2 -C m −2 h −1 )/(µmol m −2 s −1 ) and GP max (limit of production rate when approaching infinite PAR in mg CO 2 -C m −2 h −1 ) for each measurement location per measurement date using Eq.…”
Section: Gpp Modellingmentioning
confidence: 99%
“…N 2 O budgets that are based on temporal upscaling of momentary observations risk missing N 2 O emission peaks that originate from fertilizer or manure application. However, even very short measurement intervals do not guarantee recording of all emission peaks due to the extremely high temporal (Kaiser et al, 1998) andspatial (Folorunso andRolston, 1984;Glatzel et al, 2008) variation of N 2 O fluxes. Furthermore, if we really missed peak fluxes, the difference between the intensive site and the other sites would be even higher than reported here.…”
Section: N 2 O Fluxesmentioning
confidence: 99%
See 2 more Smart Citations
“…This was to be implemented by rewetting of drained and cut-over raised bogs. Several research papers have reported both success and failures of restoration measures in cut-over raised bogs, and have discussed the causes and effects (Smolders et al 2003;Grootjans et al 2006;Glatzel et al 2008;Crushell et al 2009). The success of restoration appears to depend upon the degradation state of the drained and/or cut-over remnant peat body (Joosten 1995) as well as the diversity of the remaining vegetation and diaspores (Robroek et al 2009).…”
Section: Introductionmentioning
confidence: 99%